PENGARUH PENERAPAN MODEL PEMBELAJARAN INSTAD (INQUIRY - STAD) TERHADAP MOTIVASI DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PESERTA DIDIK KELAS VII SMPN 5 WONOMULYO KABUPATEN POLEWALI MANDAR - Nurhidayah Nurhidayah; Usman Mulbar; Asdar Asdar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2015)
The research aims to discover hether INSTAD learning model has influence towards motivation and mathematics problem solving ability of class VII students at SMPN 5 Wonomulyo Polewali Mandar district. The research was pre-experiment with one group only pretest-postest design. The results of the research showed that (1) the students’ motivation before implementing INSTAD learning model gained the average by 74.73 or in medium category, and the motivation after implementing INSTAD learning model gained verage by 101.83 or in very high category, also the improvement of the students’ learning motivation gained the average by 0.6 or in medium category, (2) the students’ ability in solving problem before implementing INSTAD learning model gained the average by 43.42 or in very low category, and the ability of solving problem after implementing INSTAD learning model gained verage by 78.95 or in medium category, also the improvement of the students’ ability in solving problem gained the average by 0.63 or in medium category, (3) the implementation of INSTAD learning model has influence towards the students’ motivation, (4) the implementation of INSTAD learning model has influence towards the students’ ability in solving problem.